Women's Participation in Election in Jombang District - Prastyawan, Agus; Lestari, Yuni; Dewi, Putri Aisyiah Rachma; Gamaputra, Gading; Mardliah, Sjafiatul (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
The struggle of women to occupy public positions is not as easy as that of men. The totality of domestic and public roles that are carried out simultaneously by women leads to multiple roles that must be played. The strength of the patriarchal culture is also a measure of the inappropriateness of women in occupying public seats, especially in politics. This misunderstanding does not only come from men and society, even many women are not aware of the roles they carry out. So far, women's participation in politics appears more often as election participants or as voting members and not many women participate in the election organizing committee. The policy of affirming the 30% quota for women's representation is not only at the level of election participants, but also applies at the level of organizing elections, starting at the central level to local committees. This has been clearly stated in Law no. 7 of 2017 concerning General Elections. This article is the result of qualitative research using data collection techniques through documentation and interviews with the Jombang KPU commissioner team. Based on the results of the research, it was found that the data on the 2019 election results related to the implementation of the election obtained unsatisfactory results, especially related to the quota for representation of women election organizers. The condition of not fulfilling the quota took place both at the KPU commissioner level, the District Election Committee (PPK), and the Voting Committee (PPS). Meanwhile at the level of the Voting Organizing Group (KPPS) it is in the condition that the 30% quota for women's representation is fulfilled.